Synthesis of Scyllatoxin‐Based BH3 Domain Mimetics with Diverse Patterns of Native Disulfide Bonds. Issue 8 (22nd August 2022) - Vince, Matthew J. K.; Holub, Justin M.
Abstract: This article outlines the design and development of scyllatoxin (ScTx)–based BH3 domain mimetics with diverse patterns of native disulfide bonds. More specifically, this method summarizes the total chemical synthesis of ScTx‐based peptides that contain zero, one, two, or three disulfide linkages, including techniques to generate variants with any combination of native disulfides. Each peptide reported herein is generated on solid‐phase support using microwave‐assisted coupling procedures, and all reaction parameters related to the peptide synthesis are described in detail. The various disulfide patterns of the ScTx‐based constructs are established during peptide synthesis and are ultimately verified by mass analysis of trypsin‐digested fragments. The BH3 domain mimetics developed herein were generated by transposing residues from the helical BH3 domain of the pro‐apoptotic BCL2 protein Bax to the α‐helix of wild‐type ScTx. Interestingly, we found that the relative binding affinities of ScTx‐Bax peptides for the anti‐apoptotic BCL2 protein Bcl‐2 (proper) were heavily influenced by the number and position of disulfide linkages within the ScTx‐Bax sequence. As a consequence, we were able to utilize ScTx‐Bax BH3 domain mimetics with varied patterns of disulfide bonds to survey how structural rigidity within the helical Bax BH3 domain affects binding to promiscuous anti‐apoptotic BCL2 proteins. More broadly, the ability to generate ScTx‐based molecules that contain any combination of native disulfide bonds expands the utility of such constructs as tools to study the molecular nature of protein‐protein interactions. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis and characterization of ScTx‐based Bax BH3 domain mimetics Basic Protocol 2 : Oxidation of ScTx‐Bax BH3 domain mimetics containing one, two, or three disulfide linkages Support Protocol : Mapping of disulfide linkages in oxidized ScTx‐Bax BH3 domain mimetics